Crop rotation and tillage affect nematode communities more than biocides in monoculture soybean - Neher, Deborah A.; Nishanthan, Tharshani; Grabau, Zane J.; Chen, Senyu Y. (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2019)
Long-term monoculture of susceptible soybeans naturally develops suppressiveness to soybean cyst nematode (SCN) Heterodera glycines if fields are not tilled or biocides applied. Nematode community indices, that integrate the responses of different taxa and trophic groups to perturbation, provide a tool to monitor the ecological status of soil communities. We tested the hypothesis that soil suppressiveness to Heterodera glycines is correlated positively to management practices that favor both greater trophic diversity (food web complexity) and a later stage ecological succession (less disturbance) within free-living nematode communities. A factorial combination of cultivation, crop rotation, and biocide application treatments were monitored for four years in a field with a history of no-till and monoculture of susceptible soybean for 15 years. Crop rotation had the greatest impact on nematode community index values followed by descending order of cultivation and biocides. Suppressive soils did have greater food web complexity, but not necessarily ecological succession. Nematode community composition was influenced by covariables nitrogen and organic matter content (mean 6.6%), but not pH or salinity. The study is novel by using a food web approach that includes multiple trophic levels rather than simply population ecology. •Relatively complex food webs correspond with suppressive soils.•Free-living nematode communities change when disease suppression is disrupted.•Suppressive soil contained a common core of bacterivores and omnivore-predators.•Crop rotation affected soil food web complexity more than cultivation and biocides.